2019
DOI: 10.1021/acs.macromol.9b01134
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessing Cross-Linked Polyurethanes by Catalyzing Carbamate Exchange

Abstract: The reprocessing or recycling of cross-linked polymers by incorporating dynamic covalent cross-links has the potential to increase their usable lifetimes and reduce their environmental impact. Polyurethanes (PUs) are among the largest class of cross-linked polymers, making up 31% of the thermosetting materials market in 2012; however, their direct recycling into similar value materials is not well developed. We demonstrate that several Lewis acid catalysts mediate urethane exchange, likely via a dissociative m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 41 publications
4
111
0
Order By: Relevance
“…In both studies, a tin-catalyst was used and the influence of the amount of the catalyst on the relaxation rate was demonstrated. When comparing the relaxation behavior of poly(thiourethane) and poly(urethane) networks, it can be observed that the activation energy, E a , is significantly lower for the former (between 70 and 100 kJ/mol) [6,7] than for the latter (around 140 kJ/mol) [13], which confirms the kinetic effect produced by the substitution of oxygen by sulfur.…”
Section: Introductionmentioning
confidence: 73%
“…In both studies, a tin-catalyst was used and the influence of the amount of the catalyst on the relaxation rate was demonstrated. When comparing the relaxation behavior of poly(thiourethane) and poly(urethane) networks, it can be observed that the activation energy, E a , is significantly lower for the former (between 70 and 100 kJ/mol) [6,7] than for the latter (around 140 kJ/mol) [13], which confirms the kinetic effect produced by the substitution of oxygen by sulfur.…”
Section: Introductionmentioning
confidence: 73%
“…For this reason, ethylene oxides and similar ether moieties are frequently found in CANs. 36,[43][44][45][46][47] One factor that is however mainly overlooked when it comes to these ether moieties is the concomitant induced polar effect on the polymer network (dynamics), which was previously reported for materials that rely on ion transport. 48,49 For example in the study by Zhao and co-workers, the differences between polar EO linkers and apolar alkyl linkers were noticeable as a significant decrease in the…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the dynamic nature of the carbamate linkage has been exploited to enable reprocessing of PUs via catalysts familiar in PU polymerizations, namely tertiary amines, Lewis acids, and organotin compounds. [ 33–39 ] In a similar vein, polyhydroxyurethanes can be reprocessed through catalyst‐free exchange of hydroxyl and carbamate functionalities. [ 40–44 ] However, reprocessing of PUs and polyhydroxyurethanes also requires high temperature and/or extended reaction times.…”
Section: Methodsmentioning
confidence: 99%